PENERAPAN PEMBELAJARAN KOOPERATIF TIPE FOLLOW-UP QUESTION UNTUK MENINGKATKAN HASIL BELAJAR ILMU PENGETAHUAN SOSIAL PADA MATERI SUMBER DAYA ALAM KITA MURID KELAS IV SDN 005 PAGARAN TAPAH DARUSSALAM KABUPATEN ROKAN HULU - NOVIANTO, DONI (Aksara Public, 2017)
This research is motivated by the low learning outcomes in the material IPS Natural Resources SDN 005 fourth grade students Pagaran Tapah Darussalam Rokan Hulu. As the researchers did attempt to solve the problem is by applying Cooperative Learning Follow-Up Question aimed at improving student learning outcomes IPS. Subjects in this study is the fourth grade students by the number of students as many as 30 people. This research was conducted in SDN 005 Pagaran Tapah Darussalam Rokan Hulu While the object in this research is Improving Learning Outcomes Social Sciences In the Matter of Natural Resources We Pupil Class IV SDN 005 Pagaran Tapah Darussalam Rokan Hulu. Based on the survey results revealed that results for students before action is obtained in classical completeness is 36%, an increase in the first cycle to 60%. While the increase also occurred in the second cycle with the classical completeness 100%